1997
DOI: 10.1016/s0925-4439(97)00044-6
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and localisation of ganglioside GM3 in human intimal atherosclerotic lesions

Abstract: Immunohistochemical examination showed that sections of intimal atherosclerotic plaques contained cells and cell clusters as well as areas of extracellular matrix specifically stained with antibodies against ganglioside GM3. No immunohistochemical staining was observed in areas bordering the plaques where there was no histological evidence of atherosclerosis. To determine whether the ganglioside GM3 deposits in the intimal plaques derived directly from plasma or were synthesised by intimal cells. intimal plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…In addition, baseline concentration of PC 34:4, PC 32:2, GM3 16:0, GM3 18:0 and total GM3 were associated with the change in CCA-IMT such that higher baseline levels were associated with greater CCA-IMT regression. GM3 accumulation has been observed in intimal atherosclerotic lesions in the carotid artery and aorta[34] and serum GM3 has been identified as a potential marker of early atherosclerosis[35]. Therefore this finding suggests that those with greater atherosclerotic burden at baseline had greater CCA-IMT regression which is consistent with our previous finding[22].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, baseline concentration of PC 34:4, PC 32:2, GM3 16:0, GM3 18:0 and total GM3 were associated with the change in CCA-IMT such that higher baseline levels were associated with greater CCA-IMT regression. GM3 accumulation has been observed in intimal atherosclerotic lesions in the carotid artery and aorta[34] and serum GM3 has been identified as a potential marker of early atherosclerosis[35]. Therefore this finding suggests that those with greater atherosclerotic burden at baseline had greater CCA-IMT regression which is consistent with our previous finding[22].…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have demonstrated the ganglioside composition involved in the development and progression of atherosclerosis (23)(24)(25). Studies have shown that GM1 and GM2 induce VSMC proliferation through ERK1/2 activation (31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a dual function of ganglioside GD3, in both cell proliferation and inhibition of cell growth in VSMC (32,33). A number of studies have demonstrated massive and excessive accumulation of GM3 in atherosclerotic lesions (23,24). Other studies reported that exogenously-supplied GM3 inhibited DNA synthesis independently of ERK1/2 activation in VSMC (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations